PENGARUH FINANCIAL LITERACY, FINANCIAL ATTITUDE, FINANCIAL SELF-EFFICACY, FINANCIAL TECHNOLOGY, LOCUS OF CONTROL, LIFESTYLE TERHADAP FINANCIAL MANAGEMENT BEHAVIOUR PADA MAHASISWA SURABAYA HOBBY MODIF MOBIL - Candra Kusuma Wijaya (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
This study aims to investigate the influence of financial literacy, financial attitude, financial self-efficacy, financial technology, locus of control, and lifestyle on the financial management behavior of Surabaya students who have a hobby of modifying cars. The sample for this study consisted of 168 Surabaya students interested in car modifications during the period from 2020 to 2022. The analysis technique employed in this study was multiple linear regression using SPSS version 26. The results of the study indicate that financial literacy has a significant effect on financial management behavior, financial attitude also has a significant effect on financial management behavior, financial self-efficacy does not have a significant effect on financial management behavior, financial technology has a significant influence on financial management behavior, locus of control has a significant influence on financial management behavior, and lifestyle does not have a significant effect on financial management behavior.